Effects of High-Impact Learning Practices: A Review - Arıkan, Simla; Dochy, Filip; Segers, Mien (Advances in Social Sciences Research Journal, 2023)
One of the biggest concerns that has come to the fore in the field of education recently is whether colleges and higher education institutions offer educational programs providing their students with the basic skills and competences necessary to meet the requirements of the globalising and rapidly changing world and the accordingly changing labour market. To answer this question, this review investigated the effects of 11 high impact practices (HIPs) based on single HIPs (RQ1), limited combinations (LC) of HIPs (RQ2), and extended combinations (EC) of HIPs (RQ3). For this study, selected 56 studies were analysed by narrative analysis. As a result, 18 different positive effects were determined on which single HIPs enhanced. Among these effects critical thinking, communication and collaboration were the most promoted ones. In addition, fourteen LC of HIPs with 17 different positive effects were detected. Communication, collaboration and career related opportunities were the most common effects of LC of HIPs. Furthermore, 16 different positive effects of EC of HIPs can be grouped under five main headings as achievement-focused effects, motivation-focused effects, competence development-focused effects, personal development-focused effects and learning process-focused effects. EC of HIPs have the most competence/skills development-focused effects with their features of developing transformative learning, leadership skills, student and faculty/peer/community interaction, critical thinking, time management and job-readiness skills. Also, the most common effects of EC of HIPs were increased student engagement and motivation, increased critical thinking, higher academic achievements, higher graduation rates and retention.